Activities of the Summer Party of the 36th Japanese Antarctic Research Expedition in 1994-1995 - Yutaka AGETA (Antarctic Record, 1995)
The 36th Japanese Antarctic Research Expedition (JARE-36) consisted of 40 wintering members and 16 summer members with one atmospheric chemist from Germany. The icebreaker SHIRASE left Tokyo on November 14,1994,and arrived at Syowa Station on December 24 via Fremantle. All cargo of about 1070t was unloaded by January 12,1995. Constructions to replace old buildings and facilities at Syowa Station and for a large HF radar system and others were carried out by February 14. For the Deep Ice Coring Project at Dome Fuji, an oversnow traverse to/from the Dome Fuji Station (77°19′S, 39°42′E, 3810m a.s.l.) was performed; the first wintering at the new station was started by 9 members from January 29. Observations on geology, geodesy, biology and others were carried out around Syowa Station, Lutzow-Holm Bay and Riiser-Larsen Massif. Observations on physical, chemical and biological oceanography, geomagnetism and others were made through the voyage of the SHIRASE from Tokyo via Antarctica to Sydney. The summer party of JARE-36 returned together with the JARE-35 wintering party to Tokyo from Sydney by air on March 28 with satisfactory results.